Analisis Framing Murray Edelman dalam Periwayatan á¸¤adÄ«th bi al-Maâ€˜nÄ - Ahmad Rohmatullah (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2017)
This article analyzes the model of narration of á¸¥adÄ«th with meaning (bi al-maâ€˜nÄ) in the perspective of framing analysis according to Murray Edelman. Analysis of framing is relevant to be applied to historical á¸¥adÄ«th with meaning (bi al-maâ€˜nÄ), where the á¸¥adÄ«th is information on the events of the Prophet Muhammad which were witnessed by various sentences and words. The concept of framing analysis is closely related to information about an event that is presented with a different editor and a different visual side. This editorial and visual diversity fosters scientific assumptions which then develop into a concept of framing analysis. The variety of traditions of the á¸¥adÄ«th narrated meaningfully is a result of the process of categorization and construction among the narrators of the á¸¥adÄ«th. Even though it is not a determinant factor, the riwÄyat bi al-maâ€˜nÄ tradition shows a different process of categories and constructs among the narrators of the á¸¥adÄ«th. The event is the same but expressed in a series of different sentences, or different words.